PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN ORANG TUA DALAM PENANGANAN KEGAWATDARURATAN KEJANG DEMAM PADA ANAK DI KELURAHAN MAHAWU KECAMATAN TUMINTING KOTA MANADO - Rukmini Harun (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
Febrile seizures or better known as fever fits in children occur due to an increase in body temperature or a high fever. The high fever itself is caused by viral or bacterial infection. An important action for a mother to take is to maintain a smooth airway by not putting anything in the mouth, either food or drink. The importance of health education in order to increase mother’s knowledge in the initial treatment of febrile seizures at home because most parents do not understand about febrile seizures and their handling. The purpose of this research was to find out the effect of health education on parents’ knowledge in handling with emergency febrile seizures in children in the 3rd neighborhood of Mahawu. This research was conducted by using a quasy experimental method with one group pretest-posttest approach. Respondents were amounted to 24 people. Data collection was done by giving questionnaires. Then, the collected data was processed by running the SPSS computer program version 16.0 to be analyzed by a Wilcoxon test with the significance level α = 0,05. From the Wilcoxon test, it was obatained that the ρ value = 0,000 < α = 0,05. It showed that Ha is accepted. The conclusion of this research is that there is an effect of health education on parents’ knowledge in handling with emergency febrile seizures in children in the 3rd neighborhood of Mahawu. It is suggested that health education can be used as form of intervention to provide education to the community in order to improve the quality of health in the community.